Pengaruh ERP Berbasis Cloud Terhadap Efisiensi Rantai Pasok - Susilawati, Yulianti Ika; Rumanto, Yuliadi; Maslahah, Ulfa; Rofi Al-Qodiri, Yusuf; Tursulistyono Yani Achsan, Harry (Universitas Singaperbangsa Karawang, 2024)
The advancement of technology has led industries to adopt it. Enterprise Resource Planning (ERP) is an information system model that integrates and automates business processes. Many studies in the ERP field range from survey papers and literature reviews to qualitative research. However, previous research has not analyzed the influence of ERP implementation on supply chain efficiency in actual industries. Therefore, this research analyzes ERP implementation to improve supply chain efficiency in the manufacturing industry using a quantitative approach. Data was collected through a questionnaire with 62 respondents, and the data analysis shows that 51,6% of ERP implementations have a positive impact on increasing supply chain efficiency.